Childhood leukemias in Mexico: towards implementing CAR-T cell therapy programs - Bustamante-Ogando, Juan Carlos; Hernández-López, Alejandrina; Galván-Díaz, César; Rivera-Luna, Roberto; Fuentes-Bustos, Hugo E.; Meneses-Acosta, Angélica; Olaya-Vargas, Alberto (Frontiers in Oncology, 2024)
Leukemias are the most common type of pediatric cancer around the world. Prognosis has improved during the last decades, and many patients are cured with conventional treatment as chemotherapy; however, many patients still present with a refractory disease requiring additional treatments, including hematopoietic stem cell transplantation. Immunotherapy with monoclonal antibodies or cellular therapy is a promising strategy for treating refractory or relapsed hematological malignancies. Particularly, CAR-T cells have shown clinical efficacy in clinical trials, and different products are now commercially approved by regulatory agencies in the USA and Europe. Many challenges still need to be solved to improve and optimize the potential of these therapies worldwide. Global access to cell therapy is a significant concern, and different strategies are being explored in the middle- and low-income countries. In Mexico, leukemias represent around 50% of total cancer diagnosed in pediatric patients, and the rate of relapsed or refractory disease is higher than reported in other countries, a multi-factorial problem. Although significant progress has been made during the last decades in leukemia diagnosis and treatment, making new therapies available to Mexican patients is a priority, and cell and gene therapies are on the horizon. Efforts are ongoing to make CAR-T cell therapy accessible for patients in Mexico. This article summarizes a general landscape of childhood leukemias in Mexico, and we give a perspective about the current strategies, advances, and challenges ahead to make gene and cell therapies for leukemia clinically available.